Intermolecular coulombic decay in small biochemically relevant hydrogen-bonded systems - Stoychev, Spas Dimitrov; Kuleff, Alexander I.; Cederbaum, Lorenz S. (Journal of the American Chemical Society, 2011)
Intermolecular Coulombic decay (ICD) is a very fast and efficient relaxation pathway of ionized and excited molecules in environment. The ICD and related phenomena initiated by inner-valence ionization are explored for H2O···HCHO, H2O···H2CNH, H2O···NH3, NH3···H2O, H2O···H2S, H2S···H2O, and H2O···H2O (p-donor···p-acceptor). This set of small hydrogen-bonded systems contains seven types of hydrogen bonding, which are typical for biochemistry, and thus its investigation provides insight into the processes that can take place in living tissues. In particular, an estimate of the ICD in biosystems interacting with water (their usual medium) is made. This decay mode is expected to be a source of low-energy electrons proven to be of extreme genotoxic nature. For the purpose of our study, we have used high-precision ab initio methods in optimizing the geometries and computing the single- and double-ionization spectra of formaldehyde−, formaldimine−, ammonia−, hydrogen sulfide−, and water−water complexes. The energy range of the emitted ICD electrons, as well as the kinetic energy of the dissociating ions produced by ICD, is also reported.